Exploring the Experiences of Parents of Children with Cerebral Palsy about Therapists' Rehabilitation Services in Ahvaz, Iran: A Qualitative Study - Fatemeh Saber-Jahromi; Mohammad Khayatzadeh-Mahani; Roya Ghasemzadeh; Shadab Shahali (Vesnu Publications, 2020)
Introduction: Dealing with a child with cerebral palsy (CP) is often accompanied by numerous limitations and troublesome parenting and long-term rehabilitation services may impose high pressure on parents. The therapists should understand the needs and expectations of parents to provide appropriate services to them. So, this study is conducted aiming to explore the experiences of parents of children with CP about therapists' rehabilitation services in Ahvaz, Iran.Materials and Methods: In this qualitative study, 10 parents of children with CP were selected through purposive sampling. Semi-structured interviews were used for data gathering. Interview questions were about the experience of parents about therapists' rehabilitation services. The data were analyzed by qualitative content analysis through constant comparative method.Results: The data analysis led to a category named "characteristics of therapists providing rehabilitation services" that was divided into three subcategories including "clinical competency, adherence to professional duties, and adherence to professional ethics". Clinical competency consisted of being scientifically certified, being experienced in the field, and masculine attitude and adherence to professional duties included parent training, understanding the parents' conditions, and attention to parents' therapeutic priorities. Finally, the adherence to professional ethics was comprised of consideration of ethical issues regarding children and parents.Conclusion: Parents of children with CP stressed the need for therapists with clinical competencies, perform professional duties, and adhere to professional ethics. Therefore, therapists could provide better services through applying and implementing these principles.